Biosynthesis of silver nanoparticles with antimicrobial and anticancer properties using two novel yeasts - Xin Liu (Nature Portfolio, 2021)
Abstract AgNPs are nanomaterials with many potential biomedical applications. In this study, the two novel yeast strains HX-YS and LPP-12Y capable of producing biological silver nanoparticles were isolated. Sequencing of ribosomal DNA-ITS fragments, as well as partial D1/D2 regions of 26S rDNA indicated that the strains are related to species from the genus Metschnikowia. The BioAgNPs produced by HX-YS and LPP-12Y at pH 5.0–6.0 and 26 °C ranged in size from 50 to 500 nm. The antibacterial activities of yeast BioAgNPs against five pathogenic bacteria were determined. The highest antibacterial effect was observed on P. aeruginosa, with additional obvious effects on E. coli ATCC8099 and S. aureus ATCC10231. Additionally, the BioAgNPs showed antiproliferative effects on lung cancer cell lines H1975 and A579, with low toxicity in Beas 2B normal lung cells. Therefore, the AgNPs biosynthesized by HX-YS and LPP-12Y may have potential applications in the treatment of bacterial infections and cancer.